2012
DOI: 10.5702/massspectrometry.a0006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Sweet Spots of Glycopeptides and Polymorphism of the Matrix Crystal in MALDI Samples

Abstract: A standard dried-droplet preparation using 2,5-dihydroxybenzoic acid (2,5-DHBA) as the matrix results in a large variation in signal intensity and poor shot-to-shot reproducibility in matrix-assisted laser desorption/ionization (MALDI). We expected that the di erences can be attributed to the nature of the crystal structures in the region of the "sweet spot" within the MALDI samples. 2,5-DHBA crystals with and without analytes on a target plate obtained by means of a dried-droplet preparation contain two polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Crystal formation and analyte incorporation are influenced by the sample preparation method and several method related parameters; e. g. it was reported that the commonly used air‐dried‐droplet method leads to poor homogeneity, while electrospray sample preparation gives evenly sized matrix crystals with well‐distributed analyte incorporation . Furthermore, a low vapor pressure of the used solvent and a longer drying time improves the crystal formation and promotes homogeneous incorporation of the analyte . However, the formation of crystal layers with a homogeneous analyte distribution is difficult to achieve when using SOMs, often resulting in analyte‐rich “hotspots” and analyte‐poor areas …”
Section: Introductionmentioning
confidence: 99%
“…Crystal formation and analyte incorporation are influenced by the sample preparation method and several method related parameters; e. g. it was reported that the commonly used air‐dried‐droplet method leads to poor homogeneity, while electrospray sample preparation gives evenly sized matrix crystals with well‐distributed analyte incorporation . Furthermore, a low vapor pressure of the used solvent and a longer drying time improves the crystal formation and promotes homogeneous incorporation of the analyte . However, the formation of crystal layers with a homogeneous analyte distribution is difficult to achieve when using SOMs, often resulting in analyte‐rich “hotspots” and analyte‐poor areas …”
Section: Introductionmentioning
confidence: 99%
“…DHB is a "cool" matrix. It can reduce undesired fragmentation of fragile analytes and is useful for measuring glycopeptides 19) and phosphopeptides. 17) e following sections discuss the e ects of matrix additives on the DHB.…”
Section: -1-2 and 1-2-2) Moreover Very Few [M+k]mentioning
confidence: 99%
“…Nishikaze et al (2012a) have investigated the crystals formed by the matrix using Raman spectrometry and found that they exist as two polymorphs. Using peptides and glycopeptides, the investigators found that the peptides were distributed in both types of crystals, whereas the glycopeptides distributed mainly to the Raman spectrum B, which is generated at the early stages of crystallization.…”
Section: B Simple Matricesmentioning
confidence: 99%